Effects of Payena dasyphylla (miq.) on hyaluronidase activity and metalloproteinases expression in interleukin-1B stimulated human chondrocytes cells - Citalingam, Kamini (2012)
Hyaluronidase is one of the target enzymes in the development of osteoarthritis (OA) disease that results from the disruption of the extracellular matrix structure in the cartilage. Although various treatments for OA have been identified, they suffer from numerous drawbacks. The drawbacks are significant as OA patients require the treatment for their entire lifetime. While there is still no curative treatment for this disease, recent studies for the prevention or treatment on OA were focused on the efficacy of natural products which are capable of ameliorating the symptoms with limited side effects. Therefore, this research aimed to study the effect of Payena dasyphylla, a selected Malaysian plants on the hyaluronidases activity, and certain matrix metalloproteinases (MMPs) expression. Prior to this, a total of 20 methanolic crude extracts (bark and leaf) were screened using a colorimetric anti-hyaluronidase enzymatic assay. Out of the plants tested, bark extracts of Palaquium gutta, Pauteria obovatta and Payena dasyphylla (100 μg/ml) showed the highest inhibitory activity against bovine testicular hyaluronidase with 88.82 ± 0.15, 90.47 ± 0.09 and 91.63 ± 0.21 percent respectively. Due to insufficient amount of samples, only Payena dasyphylla with an IC50 value of 48.75 ± 8.97 μg/ml was further studied for its effect on hyaluronidase activity in interleukin-1β (100 ng/ml) stimulated human chondrocytes cells (NHAC-kn) using the zymography method. Payena dasyphylla was then fractionated into aqueous (Aq), ethyl acetate (EA) and hexane fractions where the EA fraction which showed the highest inhibitory activity against hyaluronidase was selected for further evaluation on its capability inhibiting the gene expressions of HYAL1 and HYAL2 using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) technique. Besides evaluating the effect of Payena dasyphylla on the hyaluronidases, this plant extract was also tested on the expression of other mediators mainly on MMP-3 and MMP-13 using Western blotting method. Payena dasyphylla was then further investigated for its total phenolic and flavonoid content as well as antioxidant activity. The antioxidant activity was measured using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay whereas total phenolic content was determined using the Folin-ciocalteu’s method. Results showed that Payena dasyphylla methanolic extract (100 μg/ml) inhibited hyaluronidase activity in the cultured human chondrocyte cells in response to IL-1β (100 ng/ml) stimulation. Similarly, treatment with Payena dasyphylla EA fraction (100 μg/ml) also inhibited the HYAL1 and HYAL2 gene expressions. Cytotoxicity results revealed that both Payena dasyphylla methanolic and EA fraction did not show any concomitant effect on the NHAC-kn cell line at all concentrations tested. On the other hand, the Payena dasyphylla EA fraction also inhibited MMP-3 and MMP-13 protein expression. Interestingly, treatment without IL-1β (10 ng/ml) stimulation revealed a significant difference as MMP-3 and MMP-13 protein expressions were seen only with the presence of IL-1β inducer. In addition, Payena dasyphylla EA fraction showed the highest amount of phenolic and flavonoid content with 168.62 ± 10.93 mg GAE/g and 95.96 ± 2.96 mg RE/g respectively compared to aqueous and hexane fractions. Besides, Payena dasyphylla EA extract exhibited antioxidant activity of 82.19% at the concentration of 100 μg/ml with IC50 value of 14.10 ± 1.11 μg/ml. As a conclusion, these findings showed that Payena dasyphylla contained potential classes of compound inhibiting hyaluronidases, HYAL1 and HYAL2 gene expressions as well as MMP-3 and MMP-13 protein expressions that are responsible for the degeneration of the cartilage tissue. Therefore, this plant might serve as an alternative in formulating new generation of drugs in the management of cartilage damage.